Dientes dobles : fusión y geminación. Reporte de dos casos tratamiento interdisciplinario (2004)
ABSTRACT: In this article we report two unusual cases of permanent double teeth in the maxilla. Double teeth is a term used to describe connate teeth and includes both dental fusion and gemination. Dental fusion has been defined as the partial or complete union, during development, of two or more adjacent teeth. Gemination is defined as a single tooth bud that has attempted to divide completly or partially during development, resulting in a tooth with a single root and large bifid crown. Twinning is the formation of two equivalent teeth from a single tooth bud. Dental fusion can occur between two normal teeth or between a normal tooth and supernumerary tooth, although the latter is difficult to distinguish from gemination, if not impossible. This anomaly may be unilateral or bilateral and may affect either dentition, although the deciduous teeth are more commonly affected. Might this condition cause clinical problems related to appearance, spacing, and periodontal conditions.